Handbook of engineering practice of materials and corrosion - Eun, Jung-Chul (Springer, 2020)
This handbook is an in-depth guide to the practical aspects of materials and corrosion engineering in the energy and chemical industries. The book covers materials, corrosion, welding, heat treatment, coating, test and inspection, and mechanical design and integrity. A central focus is placed on industrial requirements, including codes, standards, regulations, and specifications that practicing material and corrosion engineers and technicians face in all roles and in all areas of responsibility. The comprehensive resource provides expert guidance on general corrosion mechanisms and recommends materials for the control and prevention of corrosion damage, and offers readers industry-tested best practices, rationales, and case studies. Provides a thorough overview of all requirements related to material and corrosion engineering in the energy and chemical industries Offers expert guidance on industrial codes and standards, including ASME, ASTM, API, AWS, and NACE Provides industry-tested best practices, rationales, and case studies.